IMPLEMENTATION OF WOMEN – BASED INTEGRATED CHILD PROTECTION - Azizah, Isnafiatul; Agustina, Isna Fitria (Journal of Geography, Regional Planning and Development, 2024)
General Background: Child protection remains a critical issue globally, with children often facing violence in environments meant to safeguard them. Effective community-based child protection programs are essential to addressing this growing concern. Specific Background: The Community-Based Integrated Child Protection Program aims to provide a coordinated approach to protecting children within local communities. However, the implementation of such programs at the village level, specifically in Tambak Kalisogo Village, Sidoarjo Regency, has not been thoroughly explored. Knowledge Gap: There is limited research on the practical implementation of community-based child protection programs, particularly in rural areas, and the role of local stakeholders in ensuring their success. Aims: This study aims to analyze the implementation of the Community-Based Integrated Child Protection Program in Tambak Kalisogo Village, focusing on the roles of various stakeholders and the effectiveness of the program in protecting children. Results: The study found that the program benefited from strong synergy among stakeholders, supported by adequate facilities and funding. A well-defined bureaucratic structure and clear Standard Operating Procedures (SOPs) ensured consistency in program execution. However, the program’s success heavily relied on continued collaboration, adequate human resources, and ongoing coordination among all involved parties. Novelty: This study provides new insights into the effectiveness of community-based child protection programs, emphasizing the importance of collaboration and coordination between stakeholders in rural settings. Implications: The findings suggest that successful child protection programs require not only adequate infrastructure and resources but also sustained stakeholder engagement and capacity-building to ensure their long-term effectiveness in protecting children from violence.